(untitled) (LACCEI, 2024)
The objective of this paper was to describe the business model of the company Ecreea Company S.A.C. of Trujillo and identify the concepts of E-business that allow proposing an online business to improve the value offer. The processes that the company has were announced and those that are around the Human Talent Management area were chosen to improve the productivity of its employees and the work environment in the organization, which is why the design of a digital platform that serves as support in terms of training is proposed, Payroll, staff turnover, etc., whose purpose is to align employees with the objectives of the company. Finally, the current situation of the company was detailed, both internally and externally, the proposed business model, the technological infrastructure was also developed along with the design of the web solution and the E-business improvement plan based on said solution.